Transgredir é inevitável: pontos de tensão entre Umbanda e Santo Daime - Gusman Neto, Celso Luz (2012)
The Santo Daime is a religion which was founded in the 1930s, however it was only in the 1980s that the Umbanda started to gain visibility in daimista worldview. It happened due to the expansion beyond the limits of the Amazon forest. Sebastião Mota de Melo was responsible for leading this expansion. He turned his group into a segment most representative among who came from the original trunk of Mestre Irineu, founder of the Santo Daime. The Santo Daime has a charismatic character as well as the combination of religious headquarters that complete their cosmology. It brings to the religion a high degree of porosity of its borders. However, given the institutional growth that experienced due to the expansion, the religion found itself in need of bureaucratized its organization, process that was named the rationalization of charisma by MaxWeber. In this process, the rules which governing the rituals and the institutional order tend to strengthen. Indeed, the main reason of the Santo Daime remained guaranteed by the drink itself, which is the central element of the rituals. This confirms that charisma is ever-present, making the process of rationalizing an even bigger challenge. When Umbanda became an integrated part of their rituals practice, the Santo Daime integrates not only its pantheon of deities, but also the trance possession. In doing this, enhances the possibility of the emergence of charisma, since the trance of possession is, in itself, an ecstatic experience. Looking in the institutional perspective, which seeks establish norms and standards to maximize control, Umbanda was not consistent. The trance of possession is an experience that takes place intensively in each individual's body, making a huge difference regarding to Mestre Irineu ritual s left, where there is a predilection for the behavior of a contrite and martial. Umbanda, in this sense, meant a loosening of control, meant delivering to the body s flow rather than the containment of impulses, meant the possibility of instituting before the instituted. Thus, the dialectic of the relationship between Umbanda in Santo Daime were emerging tension points of both institutional order as a moral one